Pollution Characteristics of Microplastics in Mollusks from the Coastal Area of Yantai, China - Liu, Jiajia; Zhu, Xiaopeng; Teng, Jia; Zhao, Jianmin; Li, Chenghua; Shan, Encui; Zhang, Chen; Wang, Qing (Bulletin of environmental contamination and toxicology, 2021)
Microplastic pollution to the marine environment is a global issue. This study investigated microplastic pollution in ten species of different mollusks. Microplastic shape and size were determined under a microscope. Additionally, the polymer types were identified using Fourier transform infrared microspectroscopy (μ-FT-IR). The results showed that the microplastic abundance varied from 0.19 to 1.76 items/g (wet weight) and 4.3 to 36.6 items/individual. Four types of microplastics were observed, including fibers, fragments, films, and pellets. Fibers smaller than 500 μm were the most common. Cellophane (CP) and polyethylene terephthalate (PET) were the main polymer types. The microplastic abundance in the buried bivalve Ruditapes philippinarum demonstrated the highest level of microplastic contamination assessed by wet weight (1.76 ± 0.95 items/g). Furthermore, the Spearman correlation test showed that there was a significant negative correlation between the microplastic abundance calculated by weight and the biometric parameters (shell length, shell height and soft tissue wet weight). Our results will provide valuable information for assessment of the potential health risks of microplastics in China’s seafood.